Reference in discourse - Kibrik, A. A. (Oxford : Oxford University Press, 2011)
This is a study of how people refer to entities in natural discourse. It contributes to the understanding of both linguistic diversity and the cognitive underpinnings of language and it provides a framework for further research in both fields.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Discourse analysis